Synthesis Of Single-Wall Carbon Nanotube Via CVD Growth Mechanism - Liu, Wei Wen (2011)
Single-wall carbon nanotubes (SWCNTs) have been produced and studied since 1993 by many researchers. One of the challenges is to establish ring addition mechanism for a wide range of reaction temperature. By doing this, the growth mechanism of SWCNTs synthesised from aromatic hydrocarbon can be fully understood. Thus, this became the priority concern of this work. This work was started with the development of a catalyst system which was able to form the highest quality of SWCNTs from decomposition of methane. Response surface methodology (RSM) was applied to optimise the reaction parameters such as reaction temperature, reaction time and reaction gas flow rate.